Eksplorasi Constructive Editing pada Film Batapatih - Fella Ridalva; Hery Sasongko; Muhamad Arief (Cinelook: Journal of Film, Television, and New Media, 2023)
The creation of this Final Project entitled "Ekplorasi Constructive Editing pada Film Batapatih " is a form of accountability for the achievement of an audio visual that applies the concept of Constructive Editing, how is the placement of two shots that have no relationship but produce new meanings and give the impression that the audience not only believes but also feel the atmosphere. This means that when watching a film, the audience doesn't just stop at just getting information, but also builds up emotional aspects. The object of the creation of this Batapatih film is a child who lacks the warmth and love of his family so when he is at home the child receives warmth and affection from the people he meets. This becomes a phenomenon of how an environment can affect the character of a child. Through this work, it provides a spectacle that can build people's way of thinking in forming character towards children.